2016
DOI: 10.5489/cuaj.3329
|View full text |Cite
|
Sign up to set email alerts
|

Leak point pressure at different bladder volumes in stress urinary incontinence in women: Comparison between Valsalva and coughinduced leak point pressure

Abstract: Introduction: We compared Valsalva leak point pressure (VLPP) in urodynamically proven stress urinary incontinence (SUI) in women at different bladder volumes; examined the relationship between VLPP and cough-induced leak point pressure (CLPP) compared by incontinence severity; and evaluated the influence of bladder volume on each leak point pressure (LPP). Methods: Women with urodynamically proven SUI who underwent serial VLPP and CLPP measurement at bladder volumes of 150, 200, 250, and 300 mL were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Based on the chronologic evolution of the recommended bladder volume (Table 1) and the evidence provided, a bladder volume of 200-250ml may express VLPP without elevating detrusor pressure and therefore reflect the internal sphincter function. Furthermore, Maximum urethral closure pressure (MUCP) can also provide additional information about urethra function in women with SUI [21,22]. Hence, further studies correlating MUCP and VLPP measured at different bladder volume can contribute in the consensus of bladder volume and VLPP measurement.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the chronologic evolution of the recommended bladder volume (Table 1) and the evidence provided, a bladder volume of 200-250ml may express VLPP without elevating detrusor pressure and therefore reflect the internal sphincter function. Furthermore, Maximum urethral closure pressure (MUCP) can also provide additional information about urethra function in women with SUI [21,22]. Hence, further studies correlating MUCP and VLPP measured at different bladder volume can contribute in the consensus of bladder volume and VLPP measurement.…”
Section: Resultsmentioning
confidence: 99%
“…He mentioned a significant decrease of VLPP from the bladder volume of 150ml to 300ml and between 150ml and maximum cystometric capacity. Similarly, Young Seo et al [21] found a decrease of VLPP at a bladder volume of 250ml compared to 150 -200ml and further indicated that a bladder volume of 200ml for the demonstration of VLPP has 50% increase in the detection of ISD. On the contrary, Petrou et al [27] observed no change in VLPP with the bladder volume and concluded that the volume in the bladder should not affect the VLPP as long as the detrusor pressure is kept at a level that does not affect the urethra.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations